Definitive‐intent intensity‐modulated radiation therapy for treatment of canine prostatic carcinoma: A multi‐institutional retrospective study. (20th December 2019) - Walz, Jillian Z.; Desai, Noopur; Van Asselt, Nathaniel; Poirier, Valerie J.; Hansen, Katherine; Selmic, Laura
Abstract: No standard of care is currently recognized for treatment of canine prostatic carcinoma (PC). This retrospective study assesses outcome following definitive‐intent, intensity‐modulated radiation therapy (RT) in dogs with PC. Medical records review was performed, including 18 patients from four institutions undergoing definitive‐intent intensity‐modulated radiotherapy to treat PC. Diagnosis was incidental in 7/18 (39%) patients. Five dogs (28%) had evidence of metastasis to loco‐regional lymph nodes at diagnosis. Seventeen patients received concurrent non‐steroidal anti‐inflammatory drugs; 15/18 (83%) patients received maximally‐tolerated dose (MTD) chemotherapy, with variable drugs and protocols employed. Total prescribed radiation dose ranged from 48 to 54 Gy (median 50 Gy) delivered as daily doses of 2.5‐2.8 Gy. One patient was euthanized prior to completing radiotherapy. Acute toxicity was observed in nine patients; Grade 1‐2 diarrhoea was the most common toxicity observed. Suspected late toxicity (urethral stricture, ureteral stricture and hindlimb oedema) was observed in three patients. Median event‐free survival (EFS) following RT was 220 days, and median overall survival was 563 days. Local progression occurred in seven patients at a median of 241 days. Median overall survival was significantly longer in incidentally diagnosed dogs (581 vs 220 days in symptomatic dogs, P = .042). EFS was significantly longer in patients treated with MTD chemotherapy (241 vs 25 days, P < .001), and significantly shorter in patients presenting with evidence of metastatic disease (109 days) vs those without (388 days, P = .008). These findings suggest that definitive‐intent radiotherapy is a valuable treatment option for local control of canine PC with moderate risk of toxicity.